Primary ciliary dyskinesia: critical evaluation of clinical symptoms and diagnosis in patients with normal and abnormal ultrastructure - Boon, Mieke (BioMed Central, 2014)
BACKGROUND: Primary ciliary dyskinesia (PCD) is a rare disorder with variable disease progression. To date, mutations in more than 20 different genes have been found. At present, PCD subtypes are described according to the ultrastructural defect on transmission electron microscopy (TEM) of the motile cilia. PCD with normal ultrastructure (NU) is rarely reported because it requires additional testing. Biallelic mutations in DNAH11 have been described as one cause of PCD with NU. The aim of our study was to describe the clinical characteristics of a large population of patients with PCD, in relation to the ultrastructural defect. Additionally, we aimed to demonstrate the need for biopsy and cell culture to reliably diagnose PCD, especially the NU subtype. METHODS: We retrospectively analyzed data from 206 patients with PCD. We compared the clinical characteristics, lung function, microbiology and imaging results of 68 patients with PCD and NU to those of 90 patients with dynein deficiencies and 41 patients with central pair abnormalities. In addition, we aimed to demonstrate the robustness of the diagnosis of the NU subtype in cell culture by data from genetic analysis. RESULTS: PCD with NU comprised 33% (68/206) of all patients with PCD. Compared to other subtypes, patients with PCD and NU had a similar frequency of upper and lower respiratory tract problems, as well as similar lung function and imaging. With the currently widely applied approach, without cell culture, the diagnosis would have been missed in 16% (11/68) of patients with NU. Genetic analysis was performed in 29/68 patients with PCD and NU, and biallelic mutations were found in 79% (23/29) of tested patients. CONCLUSIONS: We reported on the clinical characteristics of a large population of patients with PCD and NU. We have shown that systematic performance of biopsy and cell culture increases sensitivity to detect PCD, especially the subtype with NU. PCD with NU has similar clinical characteristics as other PCD types and requires biopsy plus ciliogenesis in culture for optimal diagnostic yield.